EXPLORING THE IMPACT OF INTERVENTIONS ON THE PSYCHOLOGICAL WELL-BEING OF PARENTS OF CHILDREN WITH DOWN SYNDROME IN KHYBER PAKHTUNKHWA, PAKISTAN - Ali, Sidra; Syeda Kaniz Fatima (Journal of Ayub Medical College Abbottabad, 2024)
Background: Despite the significant advancements in medical and educational fields, children with Down syndrome and their parents still encounter numerous challenges in underdeveloped countries like Pakistan, particularly in the Khyber Pakhtunkhwa area. This study hypothesized that prolific intervention programs instituted to support parents in dealing with these challenges will experience a drop in parental stress levels. Methods: Cross-sectional descriptive research was carried out using a Purposive sample approach between 15th June 2020 and 05th January 2023 to evaluate the impact of several intervention programs for parents at different special education centers in Mardan, Charsada, Naushera, Swabi, and Peshawar. The research included 105 parents who were approached through these intervention programs and the success of these programs were evaluated across five dimensions: Social, psychological, cognitive, religious, and educational aspects. The interview-based parenting Intervention Questionnaire (IBPIQ) was used to gather information concerning the efficacy of these interventions, and the parental stress scale was administered to measure parental stress. Results: The results of the study showed that there is no significant correlation between Parental intervention programs and reduced levels of parental stress. While a weak positive correlation (social impact: 0.212) was found whereas psychological p-values = 0.065, educational p-values = -0.058, cognitive p-values = -0.067, and religious impact p-values =0.101 were non-significant. Conclusion: After an extensive review of various intervention programs for parents of children with Down syndrome in Pakistan, this study concluded that these Intervention programs did not significantly benefit the parents. As a result, stress levels among Down syndrome’s parents did not lessen, regardless of their involvement in these interventions.